Peran Dalem Hardjonegaran Dalam Pelestarian Batik Indonesia Karya GO TIK SWAN - Annisa Sa’a Sakinah (Ornamen, 2022)
This study aims to describe: (1) The role of Dalem Hardjonegaran in the preservation of "Indonesian Batik" by Go Tik Swan. (2) The process of preserving "Indonesian Batik" by Go Tik Swan in Dalem Hardjonegaran. The form of this research is descriptive qualitative using data in the field to develop theories that are built. The theory used to examine this research uses the Theory of Culture according to Koentjaraningrat. Data sources used: informants, places and events, documents and archives. The sampling technique used was purposive sampling. Data collection techniques used were observation interviews, and documentation. The validity of the data used is source triangulation and informant review. Analysis of the data used is an interactive analysis model. The results show that: (1) Dalem Hardjonegaran plays an important role in the preservation of "Indonesian Batik" because that is where the center of all activities related to its preservation takes place. (2) The process of preserving "Indonesian Batik" has taken place before Go Tik Swan died, until now.